Association Between Methamphetamine Use and Psychiatric Hospitalization, Chemical Restraint, and Emergency Department Length of Stay. (21st September 2020) - Murphy, Charles E.; Wang, Ralph C.; Coralic, Zlatan; Lai, Andrew R.; Raven, Maria
Abstract: Objectives: Methamphetamine intoxication is an increasing cause of emergency department (ED) visits in the United States, particularly in the west. In San Francisco, California, 47% of patients visiting psychiatric emergency services are intoxicated with methamphetamine. Such patients often visit the ED due to acute psychiatric symptoms, yet ED‐based research investigating the outcomes and resource utilization of these visits is limited. Methods: We examined a retrospective cohort of ED patients requiring ED‐based psychiatric consultation from June 2017 to July 2018. We evaluated the association between methamphetamine visits and need for chemical restraint, psychiatric hospitalization, and length of stay (LOS). Results: We identified 2, 087 ED visits with psychiatric consults. Based on urine toxicology results and discharge diagnosis, 403 visits involved methamphetamine with or without other drugs, 480 involved other drugs without methamphetamine, and 1, 204 had no evidence of drug use. Methamphetamine visits were associated with increased odds of chemical restraint compared to visits without drug use (adjusted odds ratio [AOR] = 3.2, 95% CI = 2.1 to 5.2, p < 0.001), but not other drug visits (AOR = 1.2, 95% CI = 0.8 to 1.9, p = 0.4). Methamphetamine visits had lower odds of psychiatric hospitalization than other drug visits (AOR = 0.62, 95% CI = 0.41 to 0.95, p = 0.03) and longer adjusted LOS than visits without drug use (+4.3 hours, 95% CI = 4.1 to 8.3 hours, p < 0.001) but not other drug visits (+1.5 hours, 95% CI = −0.6 to 3.7 hours, p = 0.2). Conclusions: Methamphetamine ED visits were associated with increased odds of needing chemical restraint and of an increased ED LOS but not with psychiatric inpatient admission. These results indicate an opportunity to improve the efficiency of ED care for these patients.